PENGARUH HARGA TERHADAP VOLUME PENJUALAN MIE INSTAN GORENG PADA MINIMARKET INDOMARET MANISREJO DI KOTA MADIUN - Adrianus Widya Kristianto (Universitas PGRI Madiun, 2013)
In general, the high and low price of a commodity is very important for a trading company in selling the products so increasing its sales volume. Price is one ele- ment of a marketing strategy is used as a benchmark for consumers to obtain goods or services, so as to achieve the objectives of the company (at a profit).While sales volume is all of the sales result that can be achieved by a company and can be measured by specific units. Usually the lower price of product it can increase sales volume, while high price of product will resulting in decreased sales volume. But in fact the consumers is often assume the price is the determining factor of a product quality, high price goods is generally considered to have better quality than the goods whose have low prices. The method used in the research is quantitative, the research conducted at Minimarket espe- cially in Indomaret Manisrejo Madiun city. The data obtained from the documentation of the closing monthly data of Indomaret Manisrejo in Madiun which are contain list price and sales volume. The result of analysis data obtained in this research using regression correlation test, F test, and t test. In correlation values obtained rhit <= rtable (0,396 <= 0,444) or sig(hit) > = sig(prob) (0,84 >= 0,05), so we can conclude that H, is accepted it means there is no relationship between the price of the fried instant noodle sales volume in minimarket Indomaret Manisrejo in Madiun city. Fisher's test values obtained in Fbit< Flabe(l3,339 < 4,414) or sighil > sigprob(0,84 > 0,05). So we can conclude that Ho is accepted its means that no price impact on the sales volume of instant fried noodle on minimarket Indomaret Manisrejo in Madiun. While in regression coefficient test / test t values obtained thit< ttabel (-1,827 < 0,842) or values sighit > sigprob (0,84 > 0,05), it can be concluded that H, is accepted, it means that there is no difference price to price effect of sales volume fried instant noodle on minimarket Indomaret Manisrejo in Madiun.